2020
DOI: 10.3390/cells9092064
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Subtypes Underlying EMT-Mediated Catabolic Metabolism

Abstract: Efficient catabolic metabolism of adenosine triphosphate (ATP) and nicotinamide adenine dinucleotide phosphate (NADPH) is essentially required for cancer cell survival, especially in metastatic cancer progression. Epithelial–mesenchymal transition (EMT) plays an important role in metabolic rewiring of cancer cells as well as in phenotypic conversion and therapeutic resistance. Snail (SNAI1), a well-known inducer of cancer EMT, is critical in providing ATP and NADPH via suppression of several gatekeeper genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…Numerous studies reported that EMT is regulated by several signaling pathways, for example Notch-, Wnt-, PI3K/Akt-and NF-kB-dependent pathways (28)(29)(30). Previous studies have confirmed that the EMT enhances tumor cell mobility and invasiveness, thus, contributing to the development of chemotherapy resistance and metastasis (31,32). Additionally, breast cancer recurrence and prognosis have been reported to be affected strongly by EMT (13).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies reported that EMT is regulated by several signaling pathways, for example Notch-, Wnt-, PI3K/Akt-and NF-kB-dependent pathways (28)(29)(30). Previous studies have confirmed that the EMT enhances tumor cell mobility and invasiveness, thus, contributing to the development of chemotherapy resistance and metastasis (31,32). Additionally, breast cancer recurrence and prognosis have been reported to be affected strongly by EMT (13).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been found that in luminal A and B subtypes, PFK-1 is downregulated, implying that the glycolytic flux is diverted towards PPP and that, due to the presence of FBP1, gluconeogenesis is active and DHAP and GA3P can be recycled to fuel the PPP. On the contrary, in the basal-like subtype, both FBP1 and ACC2 are downregulated, both glycolysis and PPP have the possibility to be fueled, but in this case, due to the suppression of ACC2, which catalyzes the formation of malonyl-CoA (a strong inhibitor of CPT1), there is a boost towards OXPHOS due to the availability of metabolites from both glycolysis and PPP (DHAP and GA3P) and FAs [ 151 ].…”
Section: Emt and Metabolism In Selected Cancersmentioning
confidence: 99%
“…The invasive growth and metastatic process of cancer cells depends on the epithelial–mesenchymal transition (EMT), a complex biological mechanism. In addition to invasion, EMT in cancer is recently believed to be involved in resistance to cell death, resistance to chemotherapy, immunotherapy and radiation therapy, and stem cell properties [ 3 , 4 , 5 , 6 , 7 ]. It is known that EMT is induced by Snail, a transcriptional repressor of E-cadherin [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%